MANAJEMEN LABA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI: STUDI KASUS PADA PERUSAHAAN BUMN - Nurdhiana Nurdhiana; Triani triani; Tjandra Tirtono (JURNAL STIE SEMARANG, 2023)
Financial reports as a liaison media between management and owners are an important source of information so they must be reliable and relevant. However, financial reports are prone to being manipulated by management and can mislead users. Management can intervene in financial statements to fulfill certain objectives by carrying out earnings management. This study aims to analyze the influence of profitability, leverage, firm size on earnings management. The population in this study are state-owned companies listed on the Indonesia Stock Exchange in 2019-2021. Sampling using purposive sampling method. The data analysis technique to test the hypothesis uses moderated regression analysis. The results show that profitability has a no effect on earnings management. Leverage has a negative effect on earnings management. Firm size has no effect on earnings management.